2014
DOI: 10.3390/polym6051631
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Biocompatible Layer-by-Layer Film System Using Aptamer Technology for Smart Material Applications

Abstract: Aptamers are short, single-stranded nucleic acids that fold into well-defined three dimensional (3D) structures that allow for binding to a target molecule with affinities and specificities that can rival or in some cases exceed those of antibodies. The compatibility of aptamers with nanostructures such as thin films, in combination with their affinity, selectivity, and conformational changes upon target interaction, could set the foundation for the development of novel smart materials. In this study, the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…160 Using fluorescence microscopy, the ability of the sulforhodamine B aptamer to bind its cognate target was demonstrated while sequestered in a chitosan-hyaluronan film matrix, showing the unlimited opportunities for smart material construction through the aptamers. 160 Using fluorescence microscopy, the ability of the sulforhodamine B aptamer to bind its cognate target was demonstrated while sequestered in a chitosan-hyaluronan film matrix, showing the unlimited opportunities for smart material construction through the aptamers.…”
Section: Aptamer Conjugated Nanomaterialsmentioning
confidence: 99%
“…160 Using fluorescence microscopy, the ability of the sulforhodamine B aptamer to bind its cognate target was demonstrated while sequestered in a chitosan-hyaluronan film matrix, showing the unlimited opportunities for smart material construction through the aptamers. 160 Using fluorescence microscopy, the ability of the sulforhodamine B aptamer to bind its cognate target was demonstrated while sequestered in a chitosan-hyaluronan film matrix, showing the unlimited opportunities for smart material construction through the aptamers.…”
Section: Aptamer Conjugated Nanomaterialsmentioning
confidence: 99%
“…Actually, in linearly growth of layer thickness each bilayer interacts only with bilayers that directly neighbor it (above or below) with very little inter-penetration. However, there are systems that showed exponential increases in film thickness with each deposition cycle, this type of growth was attributed to a diffusion of polyelectrolyte "in" and "out" of the film during each bilayer step (Foster & DeRosa, 2014), which is the case of cotton porous fibers whereas polyelectrolyte diffusion is expected. The typical thickness of a linearly growing film constituted of 20 bilayers is of the order of 100 nm but the thickness of exponentially growing films can reach 10 m or more after the deposition of a similar number of layers (Richert et al, 2004) which is in accordance with the thickness values found by us.…”
Section: Polyelectrolyte Multilayer Film Preparation and Amps Incorpomentioning
confidence: 99%
“…Layer-by-Layer (LbL) assembly, developed by Decher et al in the 1990s, has been proven to be a simple but effective way to prepare thin films, coatings, or microcapsules with fine-tuned structures and components, showing potential for application in various areas [1] . Numerous parameter such as solution parameters (i.e., pH value, ionic strength and temperature) [2] , operational parameters (i.e., dipping time and rinsing time) [3,4] and polymer parameters (i.e., molecular weight and concentration) [5] are affecting the assembly growth and morphology of LbL thin film. Most naturally occurring polymer in the world is cellulose, which represents approximately 1.5 × 10 12 tons yearly.…”
Section: Introductionmentioning
confidence: 99%